Integrating Life Skills into Pencak Silat Training Program for Positive Youth Development - Cahyani, Yurin Rachmatika (Universitas Pendidikan Indonesia, 2020)
The main purpose of this study was to investigate the effect of integrating life skills into pencak silat training for positive youth development. The method used in this study was the matching only-pretest-posttest control group design. The instrument used was the Life Skills Scale for Sport (LSSS). The results showed that there were significant differences among the group integrating life skills in pencak silat training programs, Â the group not integrating life skills in pencak silat training programs, and groups that did not involve in sports training for positive youth development. The group integrating life skills in pencak silat training programs and the group that did not integrate life skills in pencak silat training programs were better than the group that did not practice pencak silat training programs. On the other hand, a better influence on positive youth development occurred in the group integrating life skills in pencak silat training programs compared to the group that did not integrate life skills in pencak silat training programs.